2010
DOI: 10.1371/journal.pgen.1001012
|View full text |Cite
|
Sign up to set email alerts
|

Multi-Variant Pathway Association Analysis Reveals the Importance of Genetic Determinants of Estrogen Metabolism in Breast and Endometrial Cancer Susceptibility

Abstract: Despite the central role of estrogen exposure in breast and endometrial cancer development and numerous studies of genes in the estrogen metabolic pathway, polymorphisms within the pathway have not been consistently associated with these cancers. We posit that this is due to the complexity of multiple weak genetic effects within the metabolic pathway that can only be effectively detected through multi-variant analysis. We conducted a comprehensive association analysis of the estrogen metabolic pathway by inter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
55
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 39 publications
(60 citation statements)
references
References 37 publications
5
55
0
Order By: Relevance
“…The SNPs/genes within the androgen-to-estrogen conversion pathway, which are included in the current study, represent a subset of SNPs/genes from a parent study of the entire estrogen metabolism pathway [4].…”
Section: Gene and Haplotype Tagging Snp Selectionmentioning
confidence: 99%
See 4 more Smart Citations
“…The SNPs/genes within the androgen-to-estrogen conversion pathway, which are included in the current study, represent a subset of SNPs/genes from a parent study of the entire estrogen metabolism pathway [4].…”
Section: Gene and Haplotype Tagging Snp Selectionmentioning
confidence: 99%
“…Numerous genetic association studies addressing association with cancer risk and genes in the estrogen metabolism pathway have been reported with conflicting results, probably reflecting the low penetrance of mutations in genes within the estrogen metabolism pathway, suboptimal study designs, underpowered studies or a combination of these factors [1][2][3]. We have recently been able to show, using a pathway approach, that there is an association between breast cancer risk and some of the genes involved in the androgen-to-estrogen conversion pathway (a sub-pathway of the complete estrogen metabolism pathway), particularly for the risk of estrogen receptor(ER)-positive tumours [4]. Gene-based analysis indicated that CYP19A1 was the major contributor to the observed association.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations